2012
DOI: 10.1021/jp3104535
|View full text |Cite|
|
Sign up to set email alerts
|

On the Covalent Character of Rare Gas Bonding Interactions: A New Kind of Weak Interaction

Abstract: At the averaged quadratic coupled-cluster (AQCC) level, a number of selected rare gas (Rg) containing systems have been studied using the quantum theory of atoms in molecules (QTAIM), natural bond orbital (NBO), and several other analysis methods. According to the criteria for a covalent bond, most of the Rg-M (Rg = He, Ne, Ar, Kr, Xe; M = Be, Cu, Ag, Au, Pt) bonds in this study are assigned to weak interactions instead of van der Walls or covalent ones. Our results indicate that the rare gas bond is a new kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
99
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 84 publications
4
99
1
1
Order By: Relevance
“…1), there has been significant renewed interest in trying to establish if it is possible to synthesise the first stable helium-containing molecule, with molecules containing coinage metal halides currently being the most promising. [2][3][4][5] Interestingly, for these coinage metal halide complexes, the binding energy of helium was greater than neon in the respective molecules, although argon was more strongly bound than both neon and helium; the NeAuF complex has now been identified experimentally. 6,7 The binding energy of a helium atom was greatest in HeCuF, at 2270 cm −1 , and a small amount of covalency was deduced.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…1), there has been significant renewed interest in trying to establish if it is possible to synthesise the first stable helium-containing molecule, with molecules containing coinage metal halides currently being the most promising. [2][3][4][5] Interestingly, for these coinage metal halide complexes, the binding energy of helium was greater than neon in the respective molecules, although argon was more strongly bound than both neon and helium; the NeAuF complex has now been identified experimentally. 6,7 The binding energy of a helium atom was greatest in HeCuF, at 2270 cm −1 , and a small amount of covalency was deduced.…”
Section: Introductionmentioning
confidence: 95%
“…2,4 In part, the fluorine atom acts to pull electron density towards itself, thus facilitating partial donation of 1s electron density into the virtual Cu orbitals from the incoming He atom, leading to the designation of these as a new type of weak interaction. 3 Grandinetti and co-workers have explored berylliumcontaining ions as possible candidates for producing chemically bound helium atoms in XBeHe + species, where a number of X groups were examined. 8 As discussed therein, a number of workers have investigated the use of the Be 2+ cation as a "fixing agent" for He.…”
Section: Introductionmentioning
confidence: 99%
“…chemical compounds), we turn to the latter. Unfortunately, most of such connections are bound by weak forces and they may be classified as van der Waals complexes (Zou et al 2013;Cappelletti et al 2015). This is e.g.…”
mentioning
confidence: 99%
“…[40] Recently, Boggs et al [41] reported electron density analysis of a series of Ng-loaded clusters to characterize the nature of the interaction. They also considered NgBeO in their study.…”
Section: Electron Density Analysismentioning
confidence: 99%
“…Typical NgÀBe covalent and van der Waals distances can be found in ref. [41]. We have adopted these types to assign the nature of interaction.…”
Section: Electron Density Analysismentioning
confidence: 99%